ANALISIS FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN TERHADAP PERUSAHAAN JASA BUS RAJAWALI - Abadi, Dimas Langgeng; Sofian, Syuhada (Faculty of Economics and Business Diponegoro University, 2013)
The research is motivated by the increasing number of modes of public transport, especially bus routes serving routes Solo - Semarang making competition among service providers and the increasingly tighter bus provides a variety of options for consumers. While the selectedobject in this study is the bus that included Rajawali bus routes serving Solo - Semarang. The purpose of this study was to analyze the factors that influence consumer loyalty to the Rajawali busservice company. Many factors can affect consumer loyalty including price fairness, quality of service and customer satisfaction.After a literature review and preparation of hypotheses, data were collected through quantitative methods with techniques questionnaires to 120 respondents who are customers / passengers of the bus Rajawali. The method of analysis used is the Structural Equation Modeling(SEM). This study used purposive sampling techniques for sampling where they've never been on a bus Rajawali all the more than two times as well as all of the respondents have a profession /occupation as a student. From the processing of the data is obtained five hypotheses. Meanwhile, in the questionnaire also contained open-ended questions that can be useful to know the information or reasons of consumer.This study shows that price fairness and service quality have positive effect on costumers satisfaction, price fairness and service quality have no effect on customers loyalty, and customerssatisfaction has positive effect on costumers loyalty